Analisis Produksi Dan Pendapatan Usahatani Padi Sawah Di Desa Dolago Kecamatan Parigi Selatan Kabupaten Parigi Moutong - Dian Anggraeni; Lien Damayanti; Rustam Abd. Rauf (Mitra Sains, 2017)
The research intends to find out the factors that influence farming production of rice field in and to find out the income of farming production of rice filed in Dolago Village South Parigi District Parigi Moutong Regency. This Research used survey method and samples were taken through simple random method. The samples were 38 people. The data were analyzed by using SPSS 21 and Income Analysis. The research result showed that independent variables (X1-X5) simultaneously gave significant influence on the independent bariable (Y) the farming production of rice field. It can be seen from the value of F-Test 50,966 > F-Table 2,409. The results of t-test on five variables showed that partially, there were four variables that gave significant influence the farming production of rice field, they are land area, seeds, urea Fertilizer and labors. While Phonska fertilizer variable gave negative influence. The income of the farmers of rice farm in Dolago Village was IDR 18.316.637,-/1,08Ha/planting season or IDR 16.976.395,-/Ha/planting season.